Simplifique: a) ( x-5)2 - ( x-5)2
Soluções para a tarefa
Respondido por
1
a)
= (x - 5)² - ( x - 5)²
= x² - 2.5.x + 25 - (x² - 2.5.x + 25)
= x² - 10x + 25 - (x² - 10x + 25)
= x² - 10x + 25 - x² + 10x - 25
= 0
Resp.: 0
*************************************
b)
= (x + y)² - x² - y²
= x² + 2xy + y² - x² - y²
= x² - x² + y² - y² + 2xy
= 2xy
c)
c)
= (2x + 2) - 4x.(x - y)
= 2x + 2 - 4x² + 4xy = - 4x² + 2x + 4xy + 2
= (x - 5)² - ( x - 5)²
= x² - 2.5.x + 25 - (x² - 2.5.x + 25)
= x² - 10x + 25 - (x² - 10x + 25)
= x² - 10x + 25 - x² + 10x - 25
= 0
Resp.: 0
*************************************
b)
= (x + y)² - x² - y²
= x² + 2xy + y² - x² - y²
= x² - x² + y² - y² + 2xy
= 2xy
c)
c)
= (2x + 2) - 4x.(x - y)
= 2x + 2 - 4x² + 4xy = - 4x² + 2x + 4xy + 2
rodrigues55:
e essa
Perguntas interessantes
Português,
11 meses atrás
Química,
11 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Contabilidade,
1 ano atrás